Sign of the times : Framing the grievances of the 2019-2020 Hong Kong protests - Kate Mei Lam, Lai; Teresa Wai See, Ong; Ting, Su Hie (Lulu Press Inc., 2022)
The 2019-2020 Hong Kong (HK) protest movement, which was initially triggered by the HK government’s proposed bill, eventually turned into a prolonged civil resistance. Collective action frames (CAFs), which can bring legitimacy to civil disobedience and mobilise collective actions, were manifested through protest signs that “blossomed” throughout HK. The study examined intertextuality in the expression of grievances of the 2019-2020 HK protests in signs. A total of 246 protest signs from the “Lennon Walls” and social media sources from the 2019-2020 HK protests were collected for analysis of CAFs using qualitative content analysis. The analysis shows three primary CAFs: (1) “unified prodemocracy Hongkongers” which emphasises the solidarity and unity among movement actors to maintain collective actions for the protests; (2) “police brutality” which stresses HK police’s abuses of human rights in order to mobilise the readers to respond in ways that are in favour of the protests; and (3) “conscience before politics” which highlights the importance of having a conscience in view of human rights violations. The study showed that the language of the protest signs marks the target audience and further reinforces the solidarity of Hongkongers to resist the undemocratic government and fight for freedom.